2014
DOI: 10.1186/1471-2164-15-611
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome and functional analysis of two contrasting genotypes reveals key genes for cadmium tolerance in barley

Abstract: BackgroundCadmium (Cd) is a severe detrimental environmental pollutant. To adapt to Cd-induced deleterious effects, plants have evolved sophisticated defence mechanisms. In this study, a genome-wide transcriptome analysis was performed to identify the mechanisms of Cd tolerance using two barley genotypes with distinct Cd tolerance.ResultsMicroarray expression profiling revealed that 91 genes were up-regulated by Cd in Cd-tolerant genotype Weisuobuzhi and simultaneously down-regulated or non-changed in Cd-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…The results here supported our previous observation where cadmium was found to be absorbed within hours in the root cells of a Allium sativum exposed to cadmium ). Cao et al (2014), using Leadmium TM Green AM, found that preferential localization of cadmium was in root apex of the root tips of Cd-tolerant genotype 'Weisuobuzhi' in barley exposed to cadmium, suggesting that this effect was more pronounced with increasing cadmium concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results here supported our previous observation where cadmium was found to be absorbed within hours in the root cells of a Allium sativum exposed to cadmium ). Cao et al (2014), using Leadmium TM Green AM, found that preferential localization of cadmium was in root apex of the root tips of Cd-tolerant genotype 'Weisuobuzhi' in barley exposed to cadmium, suggesting that this effect was more pronounced with increasing cadmium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been already demonstrated that some chromosomal aberration may occur by non direct genotoxic effect. Cadmium is known to have indirect effects on DNA, causing strand breaks, sister chromatid exchanges, chromosomal aberrations (Cao et al, 2014;El-Habit, Moneim, 2014). Cadmium inhibited cell division and cell expansion growth, resulting in inhibition of root growth and appearance of stunted roots (Zhang et al, 2009).…”
Section: Effects Of Cadmium On the Organization Of Mt Cytoskeleton Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Once in plants, Cd can bring a host of biochemical and physiological consequences. Cd-accrued inhibited photosynthesis and impaired growth have been reported in several plants including barley, cucumber (Gallego et al, 2012;Janicka-Russak et al, 2012;Cao et al, 2014a;Asgher et al, 2015). Cd is a non-redox active metal, it can induce generation of reactive oxygen species (ROS), lead to the oxidative burst.…”
Section: Introductionmentioning
confidence: 99%
“…Cd affects many important physiological and biochemical processes in plants such as photosynthesis and nutrient homeostasis, which in turn inhibits normal plant growth and development (CLIJSTERS;VANASSCHE, 1985;CAO et al, 2014b). To defend against the detrimental effects of Cd, plants have evolved many detoxification mechanisms, including Cd chelation and vacuolar compartmentalization (HALL, 2002).…”
Section: Introductionmentioning
confidence: 99%